(3ahGFO Gdfjd HaVGFd GdNjds - (3Yd Hf YHO GdbGOQ GdMSjfj GdWHQi Gdecj GdTGaYj,J (B1070 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi CUYO UghI GdYdjG s
(3BNQgG (B:s
(3hgh QH GdYQT GdYXje hdGMhd hdGbhI EdG HGddg GdYdi GdYXje hUdi Gddg Ydi SjOfG eMeO hBdg GdWGgQjf s
(3eQJH Ydi KeGfjI ebGUOs
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B301s
Keywords: (3Gdafhf GdMQHjI h GdaQhSjIs